H2S EXPOSURE TO WORKERS IN COAL INDUSTRIES (CASE STUDY IN SURALAYA COAL YARD AND EAST KALIMANTAN COAL MINING) - Margareta Maria Sintorini (Universitas Trisakti, 2017)
Aims: This study is aimed to identify the hazards and occupational risk factors of Hydrogen sulfide as one of the most dangerous gas exposures for employees coming from coal, oil and gas companies. Hydrogen sulfide is a toxic colourless gas with a characteristic odor, soluble in various liquids including water. This gas is irritant and asphyrant that can be absorbed through lung into blood. Its inhalation exerts hard damage of respiratory tract. Methodology and Result: The method used is the analysis of questionnaires with logistic regression statistics. The numbers of respondents are 170 people from the employment population who work in coal mining and Pertamina production units. Results obtained from workers' observations and H2S sampling suggest that the most dominant source of H2S exposure hazard comes from the skim tank and DAF areas. The variables associated with shortness of breath was age (P = 0.006). As many as 17.3% of workers did not apply proper work procedures, and 30.58% of workers had experienced work accidents. Conclusion, significance and impact study: H2S are not related to complaints of dizziness or shortness of breath of workers. Specific factors related to occupational safety are long-term exposure of work factors related to complaints of shortness of breath (OR = 2,061), and factors not using PPE associated with dizziness (OR = 3,484)